2015
DOI: 10.1080/21505594.2015.1057389
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase receptor-deficient mice mount an innate immune response to and clarify respiratory viruses as efficiently as wild-type mice

Abstract: Keywords: influenza A virus, innate immune response, respiratory syncytial virus, urokinase plasminogen activator receptor (uPAR) Abbreviations: HRSV, human respiratory syncytial virus; uPA, urokinase plasminogen activator; uPAR, urokinase plasminogen activator receptor; DMEM, Dulbeccos Modified Eagles medium; BAL, bronchoalveolar lavage; dpi, days post-infection.The plasminogen activator receptor (uPAR) is required for lung infiltration by innate immune cells in respiratory bacterial infections. In order to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…We found that the levels of CD14, LPN2, CCL20, CD147, uPAR, EGF, TFF3, MIF were significantly lower, whereas those of RBP4, CXCL5, IL-8, CFD, adiponectin, and CHI3L1 were significantly higher in hospitalized patients. Interestingly, CD14, LCN2, CCL20, uPAR, EGF, MIF, CXCL5, IL-8, adiponectin and CHI3L1 have been already associated with an increased severity of influenza virus infections in mice and humans [26][27][28][29][30][31][32][33][34][35]. By contrast, the present study is the first to demonstrate that increased levels of CD147, RBP4, TFF3, and CFD are associated with hospitalization due to IAV.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…We found that the levels of CD14, LPN2, CCL20, CD147, uPAR, EGF, TFF3, MIF were significantly lower, whereas those of RBP4, CXCL5, IL-8, CFD, adiponectin, and CHI3L1 were significantly higher in hospitalized patients. Interestingly, CD14, LCN2, CCL20, uPAR, EGF, MIF, CXCL5, IL-8, adiponectin and CHI3L1 have been already associated with an increased severity of influenza virus infections in mice and humans [26][27][28][29][30][31][32][33][34][35]. By contrast, the present study is the first to demonstrate that increased levels of CD147, RBP4, TFF3, and CFD are associated with hospitalization due to IAV.…”
Section: Discussionmentioning
confidence: 51%
“…The relative levels of 102 cytokines, chemokines, and growth factors were determined using the Proteome Profiler Human XL Cytokine Array Kit (R&D Systems Inc., USA) according to the manufacturer's instructions. Importantly, this immunoassay was chosen because it includes several biomarkers (e.g., CD14, LCN2, CCL20, uPAR, EGF, MIF, CXCL5, IL-8, adiponectin and CHI3L1), which were previously associated with severe IAV infections [26][27][28][29][30][31][32][33][34][35]. The results were analysed using ImageJ software.…”
Section: Methodsmentioning
confidence: 99%
“…PLAU/PLAUR system was induced in current study, the finding that is inconsistent with previous reports [ 15 , 17 ]. PLAUR plays a role in infiltration of immune cell is lung bacterial infection although didn’t show similar role in RSV and influenza using murine models [ 56 ]. Coagulation plays an essential role in control and clearance of the infection.…”
Section: Discussionmentioning
confidence: 99%
“…High SuPAR levels are found not only in the plasma/serum of HIV-infected individuals, but also in the central spinal fluid of patients with neurological complications ( Sidenius et al, 2004 ; Sporer et al, 2005 ; Nebuloni et al, 2009 ). In contrast, only minor differences were observed between wild type and uPAR null mice, infected with the HRSV influenza virus, indicating that the uPAR does not play a major role neither in the modulation of virus replication nor in the innate immune response against influenza infections in vivo ( Ramos et al, 2015 ). The process of virion assembly, budding, and release from the plasma membrane has been very well characterized; it is known that in T lymphocytes the HIV virions budding occurs in lipid rafts whereby host cell cholesterol, sphingolipids, and GPI-linked proteins are incorporated into the viral envelope ( Nguyen and Hildreth 2000 ; Ono and Freed 2001 ).…”
Section: Bacterial and Viral Infectionsmentioning
confidence: 99%